2013
DOI: 10.1073/pnas.1211667110
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis nanodomain-delimited ABA signaling pathway regulates the anion channel SLAH3

Abstract: The phytohormone abscisic acid (ABA) plays a key role in the plant response to drought stress. Hence, ABA-dependent gene transcription and ion transport is regulated by a variety of protein kinases and phosphatases. However, the nature of the membranedelimited ABA signal transduction steps remains largely unknown. To gain insight into plasma membrane-bound ABA signaling, we identified sterol-dependent proteins associated with detergent resistant membranes from Arabidopsis thaliana mesophyll cells. Among those,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
194
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(205 citation statements)
references
References 52 publications
9
194
0
2
Order By: Relevance
“…Moreover, immunoelectron microscopy experiments have revealed that lateral segregation of lipids and proteins occurs at the nanoscale level at the tobacco PM, thus correlating detergent insolubility with membrane domain localization of presumptive raft proteins (Raffaele et al, 2009;Furt et al, 2010;Demir et al, 2013). Together, these data point to the existence of specialized lipid domains in plants.…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…Moreover, immunoelectron microscopy experiments have revealed that lateral segregation of lipids and proteins occurs at the nanoscale level at the tobacco PM, thus correlating detergent insolubility with membrane domain localization of presumptive raft proteins (Raffaele et al, 2009;Furt et al, 2010;Demir et al, 2013). Together, these data point to the existence of specialized lipid domains in plants.…”
mentioning
confidence: 67%
“…Similarly, plant-based immunoelectron microscopy experiments have revealed partitioning of both the lipid phosphatidylinositol 4,5-bisphosphate into 25-nm clusters on the PM of tobacco BY2 cells (Furt et al, 2010) and the protein flotillin into clusters of less than 100 nm on the PM of Arabidopsis roots apices (Li et al, 2012). In addition, the protein remorin was observed by immunoelectron microscopy in domains of about 80 nm in the cytosolic leaflet of the membrane of tobacco leaves (Raffaele et al, 2009) and was more recently localized by stimulated emission depletion microscopy within domains of 97 nm in Arabidopsis, whereas the apparent size of these domains was about 250 nm, using classical confocal microscopy (Demir et al, 2013). Similarly, the heterogeneity of RGR values that we observed could correspond to domains of 100 nm or less.…”
Section: Cryptogein Induces a Spatial Rearrangement Of The Pm Order Lmentioning
confidence: 99%
See 1 more Smart Citation
“…ABA modulates both ion channel activity and gene expression in guard cells. Previous studies suggested that ABA-dependent activation of anion channels occurs within a nanodomain in the plasma membranes (Demir et al, 2013). By contrast, it remains unclear where the ABA signal is perceived and how the signal is transmitted to the nucleus in the ABA signaling pathway for gene regulation.…”
Section: Discussionmentioning
confidence: 89%
“…SLAC1, together with SLAC1 HOMOLOGOUS3 (SLAH3), represent the molecular determinants for S-type anion channel activity in guard cells (Geiger et al, 2009b(Geiger et al, , 2010(Geiger et al, , 2011, while in mesophyll cells, S-type anion channel activity appears to be driven by just SLAH3 (Geiger et al, 2009b(Geiger et al, , 2010(Geiger et al, , 2011Demir et al, 2013). Both the SLAC1 and SLAH3 channels interact with distinct kinasephosphatase pairs shown to be associated with water stress signaling (Geiger et al, 2009b(Geiger et al, , 2010(Geiger et al, , 2011Brandt et al, 2012;Scherzer et al, 2012).…”
Section: Introductionmentioning
confidence: 99%